ANALISIS SPASIAL PH DAN TEMPERATUR TANAH SAWAH BERIRIGASI MENGGUNAKAN METODE IDW - Hidayatullah, Haidhar Arvin; Fahmi, Ahmad Roshikul; Ghifari, Firdaus Al (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
This study aimed to analyze the spatial variability of soil pH and soil temperature in irrigated paddy fields using a Geographic Information System (GIS) approach in Pakukerto Village, Sukorejo District, Pasuruan Regency. However, conventional management often overlooks the spatial heterogeneity of soil properties within irrigated schemes, erroneously assuming uniformity due to water distribution. The research was conducted using a field survey method with a descriptive–spatial approach. Soil pH and soil temperature were measured directly at 25 sampling points distributed across five areas using a soil tester, while the geographic coordinates of each sampling point were recorded using a global positioning system device. The collected data were processed and spatially analyzed using GIS software. Spatial interpolation was performed using the Inverse Distance Weighting method to generate continuous distribution maps of soil pH and soil temperature. The results showed that soil pH in the irrigated paddy fields ranged from acidic to alkaline conditions, while soil temperature varied between 25 and 34 °C, with a generally homogeneous spatial pattern and several localized zones exhibiting higher temperatures. The observed spatial variability indicated that land conditions were not uniform across the study area. The spatial mapping of soil pH and soil temperature provided valuable information for site-specific land management and supported the implementation of precision agriculture in irrigated paddy fields. These findings demonstrate that rapid spatial assessment using deterministic interpolation is a viable, cost-effective strategy for diagnosing soil constraints in similar smallholder tropical agroecosystems.